A crise financeira mundial de 2008 e seu impacto na política de dividendos das companhias brasileiras - Wickboldt, Leandro Araújo (Universidade do Vale do Rio dos Sinos, 2011)
The dividend policy has been one of the most controversial subjects in corporate finance in the past years, mainly about its definition to affect or not the firms value. As the dividend policy is one of the issues not yet fully solved in corporate finance, the aims of this study were to identifies which factors influenced the dividend policies of Brazilian firms traded on the BM & F Bovespa, between 1995 and 2009, and to observe how behaved such policies before the international financial crisis by 2008/2009. Was applied a multiple linear regression on panel data in the aggregate sample and segmented by sector to the purpose of identifying factors, and difference of means test to examine the effect of the crisis. In the present study, which was as dependent variable dividend policy, replaced the term dividends for proceeds, because this last covers the entire distribution in cash, compared to net earnings, involving also the interest on equity, called Pay Out (PO). The results indicated a negative relationship between return and PO and positive relationship between debt and PO, both significant. While the factors size, investment and financial slack did not showing statistical significance in relations with the PO. Both return and debt, showed signs of influence, unexpected, contrary to results found in previous studies. In contrast, the PO passed resulted positively related with PO current, with statistical significance, as expected. Finally, the effects of the crisis did not changing significantly the PO's. The study has ratified one of the results of Lintner (1956), valid even today in many markets, also found in many other studies, namely: evidences that firms tend to follow dividends policy stable and pleasant to the look of markets and investors.
Keywords: Política de proventos; Dividendos; Finanças corporativas; Dividends policy; Pay out; Corporate financial; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis